BARONGAN JOGO ROGO DALAM TRADISI SELAPAN DINO - Efendi, Junarto; Kusumastuti, Eny (Jurnal Seni Tari, 2013)
The ceremony selapan dino is traditional ceremonies exercised regularly by villagers Gabus Pati starch every friday night wag e. Friday wage was a day of being believable villagers Gabus as days of difficult to obtain rejeki, so we needed held a ceremony selapan dino which aims to launch rejeki. The ceremony selapan dino to be held every 35 days, by villagers Gabus. The ceremony selapan dino in an hereditary manner alw ays performing barongan  jogo  rogo   as  requirement  of   the  organizing  of   ceremonies  selapan  dino.   The  subjects  in  research  is:  how  do  you  study textual  and contextual the art of barongan jogo rogo in the tradition of selapan dino in the village of Gabus Pati starch. Textual study focused on the form of a show barongan jogo rogo in selapan dino, the study of contextual focused on function barongan jogo rogo in selapan dino. A me thod of research used in this research using methods qualitative.  The technique of collecting data covering  the technique of observation, the technique of interviews and engineering  documentation.  Engineering  analysis  of  data  in   research   is  the  reduction  of  data,  presentation  of  data  and the  wi thdrawal  of   the conclusion. Research revealed that the art of barongan jogo rogo in the village of Gabus Pati starch appear around 1980 which was initiated by the father  who  was.  Textual  study  art  barongan  jogo  rogo  in  selapan  dino  focused  on  form  consisting   of  a  theme, a  performer  (  inv estors  ), accompaniment ( vote ) place stage, motion, a way ( fashion, dressing, the property and the offerings ) and the audience. An art form barongan jogo rogo in selapan dino different with a gig barongan jogo rogo served as a whole. Barongan jogo rogo in the tradition of selapa n dino served in the form of mobile convoy village of Gabus. Study contextual the art of barongan jogo rogo in selapan dino can be known that baro ngan jogo rogo serves as a means of a ritual. The function of a ritual namely as a means of turning balah and ruwatan.A  form of turning balah villagers Gabus namely by  giving  wisit  to  barongan  one  goes  home,  while   the  aim  of  turning  balah  to  villagers  Gabus  escape from  calamity  misfortune;   distress  and obstruction. A form of ruwatan villagers Gabus namely mengarak barongan roving village as figures of protector of villagers Gabus. Suggestions in this research are villagers Gabus must remain hold staging barongan jogo rogo on tradition selapan dino as a form of love tow ards art barongan and efforts to the preservation of culture. Culture and tourism agency should be more can promote tradition selapan dino to other region via the internet, salebaran or newspapers so that tradition selapan dino can known to the territory of another